Chaplain Care in the Intensive Care Unit at the End of Life: A Qualitative Analysis - Ian McCurry; Pauline Jennett; Jimin Oh; Betty White; Horace M. DeLisser (Palliative Medicine Reports, 2021)
Background: The provision of spiritual care is a key component of high-quality patient-centered care, particularly in the intensive care unit (ICU). However, the integration of spiritual care into the care of patients in the ICU is variable, especially at the end of life, which may be due in part to poor or incomplete provider knowledge of the work of chaplains. Objective: To characterize the care and services provided by chaplains to patients in an ICU at the end of life and/or their families. Design: A retrospective chart review was performed to identify all patients admitted over a three-month period to an ICU who had visits with a chaplain and an ICU course that ended in death, discharge to a palliative care facility or discharge to hospice. Subjects/setting: Twenty-five chaplains at a U.S. medical center. Measurements: Qualitative analysis was performed using directed content analysis on the notes written by the chaplains. Results: Qualitative analyses of the chaplain notes revealed four broad themes regarding the activities of chaplains in the ICU with respect to patients and families. These were that chaplains provide comfort to patients and family facing the end of life, provide prayers with a variety of purposes, assist in supporting family members through complex medical decision making, and provide connections to appropriate resources. Conclusions: Chaplains contribute to the care of patients in the ICU through a wide range of activities that demonstrate the unique intermediary and collaborative role chaplains can play within the health care team at the end of life in the ICU.